Prognostic Utility of Histological Growth Patterns of Colorectal Lung Oligometastasis - Son Jae Yeong; Min Gyoung Pak; Hyoun Wook Lee; Seung Yeon Ha; Mee Sook Roh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2018)
Background Patients with resectable colorectal lung oligometastasis (CLOM) demonstrate a heterogeneous oncological outcome. However, the parameters for predicting tumor aggressiveness have not yet been fully investigated in CLOM. This study was performed to determine the prognostic value of histological growth patterns in patients who underwent surgery for CLOM. Methods The study included 92 patients who were diagnosed with CLOM among the first resection cases. CLOMs grow according to three histological patterns: aerogenous, pushing, and desmoplastic patterns. The growth patterns were evaluated on archival hematoxylin and eosin-stained tissue sections. Results The aerogenous pattern was found in 29.4% (n=27) of patients, the pushing pattern in 34.7% (n=32), the desmoplastic pattern in 6.5% (n=6), and a mix of two growth patterns in 29.4% (n=27). The size of the aerogenous pattern was significantly smaller than that of metastases with other patterns (p=.033). Kaplan-Meier analysis demonstrated that patients showing an aerogenous pattern appeared to have a poorer prognosis, which was calculated from the time of diagnosis of the CLOM (p=.044). The 5-year survival rate from the diagnosis of colorectal cancer tended to be lower in patients with an aerogenous pattern than in those who had a non-aerogenous pattern; however, the difference was marginally significant (p=.051). In the multivariate Cox analysis, the aerogenous pattern appeared as an independent predictor of poor overall survival (hazard ratio, 3.122; 95% confidence interval, 1.196 to 8.145; p=.020). Conclusions These results suggest that the growth patterns may play a part as a histology-based prognostic parameter for patients with CLOM.